HISTOPATHOLOGY OF KIDNEY AND INTESTINE OF TILAPIA (Oreochromis niloticus) FED WITH HERB FERMENTED FEED AFTER CHALLENGE OF Streptococcus agalactiae - Al Furqon, Abdullah; Riauwaty, Morina; Luskityowati, Iesje (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
The natural ingredients' potential as immunostimulants is a plant Curcuma and Aromatic ginger. This research was conducted from March to June 2022 in the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, Universitas Riau. Histological preparations were carried out at the Bukittinggi Veterinary Center (BVet). This research aimed to know the structure of the Kidneys and Intestines of tilapia by adding herb-fermented feed to prevent Streptococcus agalactiae infection. This research was an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications. This treatment of the study was; NC (were not immersed and infected), PC (were not immersed in fermented herbs solution but infected of S.agalactiae), T1 (Giving 100 mL/kg fermented herbs), T2 (Giving 125 mL/kg fermented herbs), T3 (Giving 150 mL/kg fermented herbs). The fish used were 6 - 7 cm in size and reared with a stocking density of 1 fish/3 L of water and kept for 46 days. Fish were challenged with S.agalactiae bacteria with a density of 108 CFU/mL at a dose of 0.1 mL/head intramuscularly on day 32, after which the fish were reared again until day 46. Changes that occur in the kidneys of fish are hemorrhage, hypertrophy, and necrosis, while in the intestines there are histological changes in the form of haemorrhage, edema, vacuole degeneration, and necrosis. The results show that the feeding containing the herbal medicine of Curcuma and Aromatic ginger fermented affected the improvement of the histological changes in the kidneys and intestines of tilapia.